Wood degrading fungi - Salmiah, Ujang; Wong, Andrew H.H; Jones, E.B.Gareth (Mushroom Research Centre, University of Malaya & Ministry of Natural Resources and Environment, 2007)
This chapter gives an account of wood biodegradation, particular decay studies in Malaysiawhich has focused on evaluating the wood decay potential of selected basidiomycetes(brown and white rot fungi), ascomycetes and anamorphic fungi (sap stain fungi and softrot species) and in relation to wood protection. Studies, of lignin degrading enzymesproduced by selected basidiomycetes are at an early stage of research in Malaysia andfurther studies are warranted. Tests to determine the durability of bamboo to wood decayfungi have been undertaken and results indicate that it falls between that of birch and pine,largely attributed to the lignin content of each timber.